The Effect of Physical Exercise Training on Neck and Shoulder Muscle Function Among Military Helicopter Pilots and Crew: A Secondary Analysis of a Randomized Controlled Trial - Murray, Mike; Lange, Britt; Søgaard, Karen; Sjøgaard, Gisela (Frontiers in Public Health, 2020)
Background: This study presents secondary outcome analyses, in terms of muscle function (i.e. maximal voluntary contraction, MVC, and rate of torque development, RTD) from a parallel group, single blinded, randomized controlled trial introducing a physical exercise training intervention to reduce neck pain among military helicopter pilots and crew-members. Methods: Participants (50 pilots, 58 crew-members) were recruited from the Royal Danish Air Force and randomized to either an exercise-training-group (ETG;n=35) or a reference-group (REF;n=34). Participants in ETG received 20 weeks of self-administered exercise training specifically tailored to target the neck and shoulder muscles. REF received no training. Outcome: 1) MVC was measured for cervical extension and flexion as well as shoulder elevation and abduction, 2) RTD was measured for cervical extension and flexion. Adherence to training was self-reported and categorized as regular if performed at least once a week. Results: MVC for cervical extension was significantly increased at follow-up in ETG (37.5 ± 11.2 Nm at baseline, change: 2.1 ± 8.3 Nm) compared to REF (38.1 ± 10.7 Nm at baseline, change: -2.4 ± 6.8 Nm) according to intension-to-treat analysis (p=0.018). Likewise, RTD was significantly increased in ETG for cervical extension (149.6 ± 63.3 Nm/s at baseline, change: 14.7 ± 49.0 Nm/s) compared to REF (165.4 ± 84.7 Nm/s at baseline, change: -16.9±70.9 Nm/s) (p=0.034). The cervical extension/flexion MVC-ratio was significantly different at follow-up (p=0.039) between ETG (1.5 ± 0.5 at baseline, change: -0.0 ± 0.3) compared to REF (1.5 ± 0.5 at baseline, change: -0.2 ± 0.4). Per-protocol analysis of MVC, including only participants in ETG with regular training adherence (n=10), showed a significant increase for cervical extension (33.2 ± 7.3 Nm at baseline, change: 6.0 ± 5.4 Nm) and shoulder elevation right side (143.0 ± 25.8 Nm at baseline, change: 15.8 ± 18.1 Nm). Conclusion: Physical exercise training significantly improved MVC and RTD in the upper neck extensors. Only approximately 1/3 of participants in ETG adhered to training regularly, which likely attenuated the effectiveness of the training intervention on neck and shoulder muscle function. Future studies should focus on the practical implementation of self-administered exercise training to improve adherence.